Outbreak of melioidosis and leptospirosis co-infection following a rescue operation - Mohamed, Mohamed Sapian; M. T., Khairi; How, Soon Hin; Ramalingam, Rajalingam; Abdul Karim, Sahhir; Abdul Rahman, Norazah; Verasahib, Khebir; Ab Rahman, Jamalludin (Malaysian Medical Associations, 2012)
We analyzed the epidemiological data of all people who were involved in the search and rescue operation in Lubuk Yu, a natural recreational forest with waterfall and stream. The hospital admission records of the cases who fulfilled the case definition and the environmental samples result taken at Lubuk Yu recreational area were studied. 153 people were exposed to this outbreak, 85 (55.5%) were professional rescuers from various government agencies and 68 (44.5%) were villagers. 21 fulfilled the case definition. Ten cases were confirmed melioidosis, six melioidosis alone and four coinfected with leptospirosis. There were eight deaths in this outbreak, seven were villagers and one professional rescuer. Overall case fatality was 70%. All confirmed melioidosis cases and seven who died had diabetes mellitus. The morbidity rate were higher among the villagers, 23.5% compared to professional rescuers, 5.9%. The case fatality rate were also higher in this group which was 100% compared to 33.3% in professional rescuers. The soil and water samples in Lubuk Yu recreational area were positive for leptospira and Burkholderia pseudomallei. The presence of co-infection and co-morbidities especially diabetes mellitus among the exposed led to the high mortality in this outbreak hence a high index of suspicion is important among the healthcare professionals in the management of melioidosis cases. To avoid similar incident in future, search and rescue operation should be only conducted by professional rescuers with appropriate personal protective equipment. A register of rescuers should be maintained for surveillance and follow up if necessary.